Fuzzy logic as a prerequisite for formulating inclusive public policies in Colombia - Giraldo Jiménez, Edier Adolfo; Garcés Giraldo, Luis Fernando; Giraldo Zuluaga, Conrado de Jesús (International Journal of Aquatic Research and Environmental Studies, 2026)
The research question that this article, as a result of the investigation, seeks to answer is: To what extent is it pertinent to apply the premises of fuzzy logic in the implementation of inclusive public policies in Colombia? In accordance with this question, the general objective is to analyze the feasibility of applying fuzzy logic in the implementation of inclusive public policies in Colombia. To achieve the stated objective and address the research question, it is necessary to initially examine three categories, namely: public policy, inclusion, and fuzzy logic. Subsequently, the categories of neuroscience, neurotechnology, and artificial intelligence will also be addressed, given that the principles and main structural elements for a public policy on neuroscience and artificial intelligence will be presented. The article will be developed in three main stages: first, an understanding of the concept of public policy will be addressed, followed by that of fuzzy logic; next, the concept of inclusion will be studied, as a development, consequence, and application of the principle of the included third; and finally, the principles and structural elements for a public policy on neuroscience and artificial intelligence will be described in an enumerative manner. The main conclusion is that, indeed, due to the real existence of risks and threats posed by the development of neuroscience, neurotechnology, and artificial intelligence, it is necessary to formulate and design comprehensive public policies that, through the application of the principle of the included third, establish mechanisms for the protection of rights.
Keywords: Inclusion; fuzzy logic; neuro-rights